(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The objective of this study was to investigate the causal relationship and effect of creative economy development of community enterprises. The results indicated that 1) The creative economic development in terms of knowledge, education, creativity, and intellectual property use had a statistically significant positive impact on the operational efficiency of community enterprises. 2) The impact of creative behavior on the opportunity exploration, and the idea generation had a statistically significant positive impact on the creative economic development of community enterprises. Leadership of ideas and applications does not have a positive impact on the operational efficiency of community enterprises. Therefore, the recommendations from this research are that 1) Government agencies should support community enterprises by adopting the concept of driving the economy based on knowledge, education, creativity, and intellectual property linked to cultural foundations. Gaining knowledge of modern society and technology/innovation in the production of unique new products and services can create economic value and added value. 2) An important common point for development is ’individuals’, so entrepreneurs and personnel in community enterprises must be developed to promote the necessary potential, which must be cooperated with the government and local organizations involved in supporting individuals.